Practices and Challenges of Academic Managers of a State Institution: Inputs for Succession Plan - Adriano, Raquel C.; Geronimo, Cecilia A.; Inasoria, Romeo D. C.; Maroma, Dolly P. (Future Science / FSH-PH Publications, 2025)
The study focuses on the practices and challenges of academic man-agers of a state institution and consequently the results can be used as inputs for a succession plan. The study is a descriptive research and utilized mixed method of both quantitative and qualitative analy-sis. Survey questionnaire and questions for interviews were con-structed and utilized purposive sampling technique for respondents and participants. All of the management practices were regularly exe-cuted while the challenges encountered were perceived demanding extra efforts to accomplish. Academic managers are expected to pos-sess various characteristics such as competency, community assis-tance, accountability, dependability, conscientiousness, familiariza-tion, and consistent struggle. The different ways of handling com-plaints/issues were as follows: organization resolution, objectivity, general references, and dialogue. The initiated programs/projects for improvement/enhancement were as follows: partnership and benchmarking, training, extension, internship programs, upgrading, support and upgrading. The training programs/ seminars needed to be attended were upgrading or professional development, and the plans for improvement were upgrading, support upgrading, and pro-ficiency.